La fumigación de herbicidas colombiana y el derecho humanitario internacional - Natalia Andrade Cadena (Universidad Hemisferios, 2017)
The Colombian Government since 2000 has been using sprayings of herbicides in large scales with the aim of destroying illegal crops of coca and poppy plants. This action has been widely criticized; therefore, there have been several studies related to this matter. In the legal area, this issue has been analyzed mainly from the human rights perspective. Nevertheless, this paper addresses this matter from a completely different standpoint. This article’s main objectives are to analyze the aerial spraying of herbicides as an act of war within the Colombian armed conflict and to critically assess its lawfulness under the rules and principles of the International Humanitarian law. In other to achieve those objectives this article gives a brief background of the analyzed practice and explains why aerial spraying of herbicides can be considered an act of war. Furthermore, the reality of this practice is compared with the rules and exceptions of the International Humanitarian Law to finally conclude that the fumigations with herbicides are an open violation of the aforementioned law.